2021
DOI: 10.21837/pm.v19i17.1002
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Sustainability Implementation for Business Corporations

Abstract: Sustainability is the current trend adopted by major business corporations in Malaysia. Abundant evidence reveals corporations are now recognizing that aligning business operation with sustainable ways adds more value. Previous literature shows sustainability has become a strategic imperative for all businesses. Apart from that, having a sustainable building in their asset portfolio contributes towards achieving the management strategic corporate goals. Therefore, this research aims to discuss what are the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Waidyasekara and Silva (2016) also mentioned a low RII indicates that the factor is less applicable and less relevant, whereas a high index indicates higher applicability, agreement, and relevance. The RII analysis also was adopted by (Fauzi et al, 2021a) in their research of The Importance of 'Sustainability Implementation for Business Corporations' that is almost similar to this research.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Waidyasekara and Silva (2016) also mentioned a low RII indicates that the factor is less applicable and less relevant, whereas a high index indicates higher applicability, agreement, and relevance. The RII analysis also was adopted by (Fauzi et al, 2021a) in their research of The Importance of 'Sustainability Implementation for Business Corporations' that is almost similar to this research.…”
Section: Methodsmentioning
confidence: 98%
“…Given these influential criteria, investors and investors-owned will eventually shift from conventional to greener buildings. In fact, a study from Fauzi et al (2021a) indicated that property management corporations may focus on green elements especially in human satisfaction management. Similar results could also be found when green design features make indoor air quality better for society's well-being (Deng & Wu, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Opoku and Lee [4] provided definitions and explanatory notes on the significance of incorporating sustainability into facilities management. Fauzi et al [28] argued that in addition to the maximisation of economic value and minimisation of economic and social costs, sustainability has become a strategic imperative for businesses as they increasingly recognise that aligning business operations with sustainable ways adds more value. Managed proactively, a SFM service can reduce costs and provide long-term value [29,30].…”
Section: Sustainable Facilities Managementmentioning
confidence: 99%
“…The green building also known as sustainable building and high performance building (Shaikh et al, 2019). The main key for green building is to minimize environmental impact and costs while maximizing occupant comfort and satisfaction (Fauzi, Johari, Zainuddin et al, 2021).One of the green residential criteria, according to Elias and Khai (2015), is the house that can achieve longterm sustainability through energy efficiency, green technology applications, rainwater collection, and recycled materials, and that it is operated with sustainable resources in order to achieve the goals of sustainable development.…”
Section: Demand For Green Residential Buildingmentioning
confidence: 99%